Invasive aspergillosis in patients with systemic lupus erythematosus: a retrospective study on clinical characteristics and risk factors for mortality. (October 2018) - Hung, ML; Liao, HT; Chen, WS; Chen, MH; Lai, CC; Tsai, CY; Chang, DM
Objective: The objective of this paper is to analyze the clinical features, outcomes, mortality risk factors, and all-cause mortalities of invasive aspergillosis (IA) in patients with systemic lupus erythematosus (SLE). Methods: Medical records were reviewed to identify SLE patients with IA from January 2006 to June 2017, at Taipei Veterans General Hospital, Taiwan. A total of 6714 SLE patients were included. Clinical/laboratory parameters and treatment outcomes were analyzed. Results: Four patients (19.0%) had definite and 17 had probable (81.0%) IA. Seven patients (33.3%) survived and 14 died (66.7%). Concurrently, there were 19 pneumonias (90.5%), 17 cases of other infections (81.0%), eight bacteremia (38.1%), nine cytomegalovirus (CMV, 42.7%) and six Candida (28.6%) infections. In all 55 blood cultures, 38 (69.1%) yielded gram-negative bacilli, of which carbapenem-resistant A. baumannii accounted for eight (21.1%); 17 (30.9%) yielded gram-positive cocci, of which methicillin-resistant S. aureus accounted for six (35.3%); and vancomycin-resistant Enterococcus accounted for four (23.5%). Daily steroid dose ≥ 20 mg (hazard ratio (HR) 2.00), recent pulse steroid therapy (HR 2.80), azathioprine (HR 2.00), rituximab (HR 2.00), plasmapheresis (HR 2.00), acute respiratory distress syndrome (HR 2.00), concurrent infections (HR 5.667) and CMV viremia (HR 1.75) were higher in the fatality group. All p values were less than 0.05. Septic shock ( n  = 7, 50% in the fatality group) is the most common cause of mortality. Conclusions: High daily steroid dosing, recent pulse steroid therapy, azathioprine, rituximab, concurrent infections, and CMV viremia were mortality risk factors for IA in SLE.